Why have Australian banks survived the recent global financial crisis? - Simpson, John; Westaway, Jennifer (Curtin Business School, 2009)
Australia is a small developed country with a sophisticated, well regulated banking and financial system. Because of its smaller stock market turnover, lower capitalisation of its banking sector and smaller global interaction than other developed countries, the effect of the global financial crisis on the country has not been as great as in other developed economies. The banking regulatory framework has also had much to do with this insulation effect. This cross discipline study comments on the legal and institutional environment for banking in Australia and also reports empirical analysis of banking stock market data showing Australia’s interaction and involvement in a global context.